A therapeutic nanoparticle vaccine against Trypanosoma cruzi in a BALB/c mouse model of Chagas disease. Issue 4 (2nd April 2016) - Barry, Meagan A.; Wang, Qian; Jones, Kathryn M.; Heffernan, Michael J.; Buhaya, Munir H.; Beaumier, Coreen M.; Keegan, Brian P.; Zhan, Bin; Dumonteil, Eric; Bottazzi, Maria Elena; Hotez, Peter J.
ABSTRACT: Chagas disease, caused by Trypanosoma cruzi, results in an acute febrile illness that progresses to chronic chagasic cardiomyopathy in 30% of patients. Current treatments have significant side effects and poor efficacy during the chronic phase; therefore, there is an urgent need for new treatment modalities. A robust TH 1-mediated immune response correlates with favorable clinical outcomes. A therapeutic vaccine administered to infected individuals could bolster the immune response, thereby slowing or stopping the progression of chagasic cardiomyopathy. Prior work in mice has identified an efficacious T. cruzi DNA vaccine encoding Tc24. To elicit a similar protective cell-mediated immune response to a Tc24 recombinant protein, we utilized a poly(lactic-co-glycolic acid) nanoparticle delivery system in conjunction with CpG motif-containing oligodeoxynucleotides as an immunomodulatory adjuvant. In a BALB/c mouse model, the vaccine produced a TH 1-biased immune response, as demonstrated by a significant increase in antigen-specific IFNγ-producing splenocytes, IgG2a titers, and proliferative capacity of CD8 + T cells. When tested for therapeutic efficacy, significantly reduced systemic parasitemia was seen during peak parasitemia. Additionally, there was a significant reduction in cardiac parasite burden and inflammatory cell infiltrate. This is the first study demonstrating immunogenicity and efficacy of a therapeutic Chagas vaccine using a nanoparticle delivery system.